Relationship of Malaria Parasite Density Level in Blood with Apgar Score of Newborn Babies - Astutik, Eftyaningrum Dwi Wahyu (Indonesian Journal of Global Health Research, 2024)
Placental malaria is a serious health problem that must be treated immediately. WHO data records that 12 million pregnant women were infected with malaria throughout the world in 2019. Of the pregnant women infected with malaria, it was reported that 40% experienced placental malaria during childbirth. At the national level, it was found that the prevalence of malaria in pregnant women was 525 from the 2018 Basic Health Research results. At the provincial level, the largest contributor was Papua with a total of 2816 cases in 2020. Jayapura Regency was in 4th position with 402 cases of pregnancy malaria. Disturbances in newborn baby oxygenation caused by placental malaria are the main-focus to be resolved immediately so that efforts are made to investigate the level of relationship between the level of placental malaria parasitemia and clinical signs of impaired newborn baby oxygenation (APGAR Score) needs to be developed in order to create a formula for handling and preventing these impacts. Objective: Analyzing the relationship between the level of malaria parasite density in the blood of mothers giving birth and APGAR Score of newborn babies. Method: This research is descriptive correlational research. The total population was 36 mothers with a history of malaria during their pregnancy and research samples were taken with technique Total Sampling. Data were analyzed using a correlation test Rank Spearman with a significance level <0,05. Results: Based on correlation test Rank Spearman sig value is obtained. (2-tailed) as large as 0.00 <0.05 so that there is a significant relationship between the level of malaria parasite density in the blood of the mother giving birth with APGAR Score of newborn babies. The correlation coefficient value between the two variables is -0.658 which is included in the strong correlation category with a negative or inverse correlation direction. The higher the density of malaria parasites in the mother's blood, the lower the APGAR of newborn baby value. Conclusion: Most of the malaria parasite density levels in mothers who gave birth were in the negative category with an average APGAR score for birth defects of 8.47. There is a relationship between the level of density of malaria parasites in the blood of pregnant women and APGAR Score of newborn babies.